2012
DOI: 10.1090/s0002-9947-2012-05456-0
|View full text |Cite
|
Sign up to set email alerts
|

Describing free groups

Abstract: We consider countable free groups of different ranks. For these groups, we investigate computability theoretic complexity of index sets within the class of free groups and within the class of all groups. For a computable free group of infinite rank, we consider the difficulty of finding a basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…For purposes of characterizing complexity, we will use the following framework (note that this definition is equivalent to that given in [6]). Definition 1.…”
Section: Definitionsmentioning
confidence: 99%
“…For purposes of characterizing complexity, we will use the following framework (note that this definition is equivalent to that given in [6]). Definition 1.…”
Section: Definitionsmentioning
confidence: 99%
“…As a consequence of these technical difficulties, our knowledge of Δ 0 n -categorical structures is rather limited even when n = 2. Only recently, there has been significant progress in understanding Δ 0 n -categoricity in several specific classes, for small n. It follows from [8,30] that every free (non-abelian) group of rank ω is Δ 0 3 -categorical, and the result cannot be improved to Δ 0 2 . It is also known that every computable completely decomposable group is Δ 0 5 -categorical, and the result is sharp [13].…”
Section: Non-computable Isomorphisms Between Computable Structuresmentioning
confidence: 99%
“…In fact, the computable finitely generated groups that we have studied all have Scott sentences that are "computable d-Σ2" (the conjunction of a computable Σ2 sentence and a computable Π2 sentence). In [9], this was shown for the finitely generated free groups. Here we show it for all finitely generated abelian groups, and for the infinite dihedral group.…”
mentioning
confidence: 92%
“…Hence, there can be no simpler Scott sentence. In [9], it is shown that the free group F n on n generators has a Scott sentence that is computable d-Σ 2 . It is also shown that I(F n ) is m-complete d-Σ 0 2 , so there is no simpler Scott sentence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation